Reading Skill of Elementary School Students and Relationship to Foreign Language (German and Japanese) Contained in The Text - Danindra Diska Mariyandi; Asri Wibawa Sakti; Verra Wulandary (Universitas Komputer Indonesia, 2021)
This study aims to analyze students' interest in foreign languages such as German or Japanese. Descriptive qualitative research method. The data collection technique used descriptive qualitative and gave some reading texts to the children. The results of the study showed that the relationship between students to foreign languages other than the language that was introduced was very high, and they increasingly wanted to learn the foreign language even though they could not pronounce foreign vocabulary correctly, the foreign language contained in the Indonesian text did not make them stop reading or reading.